Anti-cancer activities of metal-based complexes by regulating the VEGF/VEGFR2 signaling pathway and apoptosis-related factors Bcl-2, Bax, and caspase-9 to inhibit angiogenesis and induce apoptosis. Issue 1 (21st November 2019) - Qin, Xiu-Ying; Wang, Ya-Nan; Liu, Han-Fu; Luo, Zhao-Hui; Zhang, Pei-Lu; Li-Fang, Huang; Liu, Mei-Rong
Abstract : Copper-based complexes exhibited multiple anti-cancer functions by regulating the expressions of Bcl-2, Bax, and caspase-9 and activating the VEGF/VEGFR2 signaling pathway. Abstract : Three novel single crystals of the metal-based complexes Cu-1, Cu-2, and Co-1 were obtained and characterized. Compared with Cu-2 and Co-1, Cu-1 showed remarkable activities of anti-cervical cancer, anti-cisplatin-resistant non-small cell lung cancer and anti-angiogenesis by downregulating the expressions of important proteins in the VEGF/VEGFR2 signaling pathway to inhibit angiogenesis and cancer cell proliferation, induce apoptosis, and suppress migration and metastasis. Moreover, Cu-1 dramatically inhibited the expression of the anti-apoptotic protein Bcl-2 and up-regulated the expressions of the proapoptotic proteins caspase-9 and Bax to induce the apoptosis of tumor cells, simultaneously decreasing the density of endothelial cells to inhibit tumor angiogenesis in cisplatin-resistant tumors.